Survey of Nursing Staff's Training on Early Warning Ability for Inpatients with "Three Infarcts and One Hemorrhage". (17th August 2021) - Shen, Zhoumin; Tang, Chanjuan; Hu, Yanjun; Cai, Yimin; Chen, Huali; Chen, Hongjiao; Liu, Yuyu; Xie, Nian
Abstract : Background and Objective. Nursing staff's cognition and training willingness on early warning ability of inpatients is an important measure to reduce the occurrence of adverse events and severe disease. In this article, we aim to understand the cognition and training needs of nursing staff in a tertiary referral center in Changsha City, Hunan Province, on the early warning ability of inpatients with myocardial infarction, pulmonary embolism, cerebral infarction, and dangerous hemorrhage (referred to as "three infarcts and one hemorrhage"). Methods . A total of 787 nursing staff in a tertiary referral center in Changsha City, Hunan Province, were selected using a convenient sampling method. We used an online questionnaire designed by ourselves to survey them. The content of the questionnaire primary included basic information, related knowledge of the nursing staff on the potential risk prediction and precontrol of inpatients with "three infarcts and one hemorrhage, " relevant information on improving early warning scores, management of clinical early warning, training needs, and training methods. Results . Over 50% of the nursing staff had little understanding about the risk warning knowledge of inpatients with "three infracts and one hemorrhage, " and the degree of understanding was related to education, job title, and working years. The nursing staff with higher education level or professional title or longer working experience have a better understanding of the risk warning knowledge of inpatients with "three infracts and one hemorrhage." Conclusion . The cognitive competence of nursing staff in a tertiary referral center in Changsha City, Hunan Province, on the early warning ability of inpatients with "three infarcts and one hemorrhage" needs to be improved. Medical institutions should actively train nursing staff on early warning ability for inpatients with "three infarcts and one hemorrhage" to improve the nursing staff's awareness and patients' safety and efficiency.